Predicting body appreciation in young women: An integrated model of positive body image. (September 2016) - Andrew, Rachel; Tiggemann, Marika; Clark, Levina
Highlights: We examine everyday activities and psychological predictors of positive body image. Body acceptance and self-compassion are related to greater body appreciation. Higher appearance media consumption is related to lower body appreciation. Self-objectification, social comparison and internalisation mediate relationships. Results highlight targets for interventions to enhance positive body image. Abstract: This study examined a range of predictors, based on previous theoretical models, of positive body image in young adult women. Participants were 266 women who completed an online questionnaire measuring body appreciation, activity participation, media consumption, perceived body acceptance by others, self-compassion, and autonomy. Potential mechanisms in predicting body appreciation assessed were self-objectification, social appearance comparison, and thin-ideal internalisation. Results indicated that greater perceived body acceptance by others and self-compassion, and lower appearance media consumption, self-objectification, social comparison, and thin-ideal internalisation were related to greater body appreciation. An integrated model showed that appearance media (negatively) and non-appearance media and self-compassion (positively) were associated with lower self-objectification, social comparison, and thin-ideal internalisation, which in turn related to greater body appreciation. Additionally, perceived body acceptance by others was directly associated with body appreciation. The results contribute to an understanding of potential pathways of positive body image development, thereby highlighting possible intervention targets.